2005
DOI: 10.1159/000087359
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-16 in Allergic Rhinitis

Abstract: Background: Interleukin-16 (IL-16) has been characterized as a chemoattractant for a variety of CD4+ T cells. Several inflammatory diseases, including allergic disorders, have been reported to correlate with IL-16. We first examined the IL-16 expression of serum and mucosal tissue in patients with allergic rhinitis. Methods: Forty-eight patients with a clinical history of house dust mite (HDM) or pollen-sensitive allergic rhinitis were included in this study. Serum IL-16 was analyzed by enzyme-linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Regarding eosinophils, IL-5 has been known as a main eosinophil chemoattractant factor, whereas it was reported that IL-16 neutralization suppressed eosinophilic chemotaxis by 60% in vitro[22], which indicates that IL-16 may also have a positive correlation with this matter. Our previous report confirmed that IL-16 serum level and local expressions in patients with allergic rhinitis were significantly correlated with the blood eosinophil percentage [13]. In addition, IL-16 can indirectly activate specific responses of eosinophils; in CD4-mediated cells, IL-16 elicits the extracellular release of RANTES and eotaxin, which then act in an autocrine fashion on CCR3 receptors to stimulate both enhanced leukotriene C 4 production and the release of IL-4 from within eosinophils [26].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Regarding eosinophils, IL-5 has been known as a main eosinophil chemoattractant factor, whereas it was reported that IL-16 neutralization suppressed eosinophilic chemotaxis by 60% in vitro[22], which indicates that IL-16 may also have a positive correlation with this matter. Our previous report confirmed that IL-16 serum level and local expressions in patients with allergic rhinitis were significantly correlated with the blood eosinophil percentage [13]. In addition, IL-16 can indirectly activate specific responses of eosinophils; in CD4-mediated cells, IL-16 elicits the extracellular release of RANTES and eotaxin, which then act in an autocrine fashion on CCR3 receptors to stimulate both enhanced leukotriene C 4 production and the release of IL-4 from within eosinophils [26].…”
Section: Discussionsupporting
confidence: 66%
“…Eosinophils and T cells are major IL-16 production sources in allergic disease [13, 27]; therefore, inhibition of their migration and activation induced by the drugs is one possible process. In the present study, both fexofenadine and ramatroban, which have antihistamine effects and anti-PGD2 or TxA2 effects, respectively, could inhibit IL-16; this suggested that IL-16 upregulation was induced through both histamine- and PGD2 (or TxA2)-mediated allergic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This IL-16 in turn recruits more eosinophils, capable of producing IL-4, to the sites of inflammation. This is believed to be one of the mechanisms underlying exacerbation of AD (Karaki et al, 2005). In acute and chronic AD lesions, the expression of IL-16 mRNA increases in epidermal keratinocytes and skin T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%